Trends in the Economic Burden of Chronic Liver Diseases and Cirrhosis in the United States: 1996–2016. (28th October 2021) - Ma, Christopher; Qian, Alexander S.; Nguyen, Nghia H.; Stukalin, Igor; Congly, Stephen E.; Shaheen, Abdel Aziz; Swain, Mark G.; Teriaky, Anouar; Asrani, Sumeet K.; Singh, Siddharth
Abstract : INTRODUCTION: The management of chronic liver diseases (CLDs) and cirrhosis is associated with substantial healthcare costs. We aimed to estimate trends in national healthcare spending for patients with CLDs or cirrhosis between 1996 and 2016 in the United States. METHODS: National-level healthcare expenditure data developed by the Institute for Health Metrics and Evaluations for the Disease Expenditure Project and prevalence of CLDs and cirrhosis derived from the Global Burden of Diseases Study were used to estimate temporal trends in inflation-adjusted US healthcare spending, stratified by setting of care (ambulatory, inpatient, emergency department, and nursing care). Joinpoint regression was used to evaluate temporal trends, expressed as annual percent change (APC) with 95% confidence intervals (CIs). Drivers of change in spending for ambulatory and inpatient services were also evaluated. RESULTS: Total expenditures in 2016 were 32.5 billion (95% CI, 27.0–40.4 billion). Over 65% of spending was for inpatient or emergency department care. From 1996 to 2016, there was a 4.3%/year (95% CI, 2.8%–5.8%) increase in overall healthcare spending for patients with CLDs or cirrhosis, driven by a 17.8%/year (95% CI, 14.5%–21.6%) increase in price and intensity of hospital-based services. Total healthcare spending per patient with CLDs or cirrhosis began decreasing after 2008 (APC −1.7% [95% CI, −2.1% to −1.2%]), primarily because of reductions in ambulatory care spending (APC −9.1% [95% CI, −10.7% to −7.5%] after 2011). DISCUSSION: Healthcare expenditures for CLDs or cirrhosis are substantial in the United States, driven disproportionately by acute care in-hospital spending.